A Core Response to the CDX2 Homeoprotein During Development and in Pathologies - Gourain, Victor; Duluc, Isabelle; Domon-Dell, Claire; Freund, Jean-Noël (Frontiers in Genetics, 2021)
Whether a gene involved in distinct tissue or cell functions exerts a core of common molecular activities is a relevant topic in evolutionary, developmental, and pathological perspectives. Here, we addressed this question by focusing on the transcription factor and regulator of chromatin accessibility encoded by the Cdx2 homeobox gene that plays important functions during embryonic development and in adult diseases. By integrating RNAseq data in mouse embryogenesis, we unveiled a core set of common genes whose expression is responsive to the CDX2 homeoprotein during trophectoderm formation, posterior body elongation and intestinal specification. ChIPseq data analysis also identified a set of common chromosomal regions targeted by CDX2 at these three developmental steps. The transcriptional core set of genes was then validated with transgenic mouse models of loss or gain of function of Cdx2. Finally, based on human cancer data, we highlight the relevance of these results by displaying a significant number of human orthologous genes to the core set of mouse CDX2-responsive genes exhibiting an altered expression along with CDX2 in human malignancies.